Measuring Nutrition Governance in Nepal: Metrics of the Management of Multisectoral Plans. - Webb, Patrick, 1959- (Tufts University. Tisch Library., 2016)
Dr. Webb explains the importance of evidence-based policy measures in government, as opposed to policy measures that sound effective but have no imperical back-up. Stats and challenges in moving forward are discussed. Delievered on Day 1 of the 2014 Scientific Symposium in Kathmandu Nepal.; Nutrition School: NIL Symposium Presentations, 2014.; Keywords: PoSHAN.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy